If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2a + 3) = 4a + 3 Reorder the terms: 3(3 + 2a) = 4a + 3 (3 * 3 + 2a * 3) = 4a + 3 (9 + 6a) = 4a + 3 Reorder the terms: 9 + 6a = 3 + 4a Solving 9 + 6a = 3 + 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. 9 + 6a + -4a = 3 + 4a + -4a Combine like terms: 6a + -4a = 2a 9 + 2a = 3 + 4a + -4a Combine like terms: 4a + -4a = 0 9 + 2a = 3 + 0 9 + 2a = 3 Add '-9' to each side of the equation. 9 + -9 + 2a = 3 + -9 Combine like terms: 9 + -9 = 0 0 + 2a = 3 + -9 2a = 3 + -9 Combine like terms: 3 + -9 = -6 2a = -6 Divide each side by '2'. a = -3 Simplifying a = -3
| -2(b+5)=-b | | 6t+8-6t+3= | | (m-4)(m+6)=0 | | m-5=-6+m | | 6(x+2)=2(2x+4) | | 3x-16(4-2x)=6 | | 24a+-22=-4(1+6a) | | p=2(89)+2(117) | | -2x-3=x+3+3x | | (x+3)+2(x-7)=3x-11 | | a(10)-8=-24 | | 2y^2+4y-198=0 | | 18-43=4(x-2)-5 | | 9x-(4x-15)=50 | | 2(4r+6)=12r+18 | | 8-9=-12 | | 3z+1=4z-8+28 | | 12(x-9)=-5-7 | | 8=(x+0.5)(x+1) | | x*x+10x=1575 | | 3x-64-32x=6 | | x+50+2x+20=90 | | -6k+7k-9k+8k= | | x+50+2x+20=180 | | 2370=320*144*15*x/35000 | | 49a^4b-14a^3b+21ab=0 | | -2(-3x+8)+5=-21 | | 4x-70=12x+2 | | 6(3a+1)-30=3(20a-4) | | 16=(x+0.5)(x+0.5) | | 2h-35=12h-10h+15 | | 2x+7x+10=11x |